2017
DOI: 10.1038/s41598-017-04766-7
|View full text |Cite
|
Sign up to set email alerts
|

TSG-6 Secreted by Human Adipose Tissue-derived Mesenchymal Stem Cells Ameliorates DSS-induced colitis by Inducing M2 Macrophage Polarization in Mice

Abstract: Previous studies have revealed that mesenchymal stem cells (MSCs) alleviate inflammatory bowel disease (IBD) by modulating inflammatory cytokines in the inflamed intestine. However, the mechanisms underlying these effects are not completely understood. We sought to investigate the therapeutic effects of human adipose tissue-derived (hAT)-MSCs in an IBD mouse model and to explore the mechanisms of the regulation of inflammation. Dextran sulfate sodium-induced colitis mice were infused with hAT-MSCs intraperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
99
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 53 publications
(57 reference statements)
7
99
0
1
Order By: Relevance
“…Although we found no significant difference in the absolute number of macrophages in TSG-6 null versus WT wounds, we did determine that macrophages in TSG-6 null wounds were skewed towards an M1 phenotype. This is in agreement with previous studies showing that and immobilized HC-HA complexes can drive macrophages to a more anti-inflammatory phenotype (Ferrer et al 2017;He et al 2013;Mittal et al 2016), and that TSG-6-producing MSCs can lower proinflammatory marker expression and increase anti-inflammatory M2 macrophages in a colitis model (Song et al 2017). From several lines of evidence, including the fact that M2 macrophages are known to promote tissue repair, and that M1 macrophages are greatly increased in chronic wounds such as diabetic ulcers, it is becoming clear that controlled regulation of macrophage phenotype is critical for proper wound healing (Hesketh et al 2017;Khanna et al 2010;Krzyszczyk et al 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Although we found no significant difference in the absolute number of macrophages in TSG-6 null versus WT wounds, we did determine that macrophages in TSG-6 null wounds were skewed towards an M1 phenotype. This is in agreement with previous studies showing that and immobilized HC-HA complexes can drive macrophages to a more anti-inflammatory phenotype (Ferrer et al 2017;He et al 2013;Mittal et al 2016), and that TSG-6-producing MSCs can lower proinflammatory marker expression and increase anti-inflammatory M2 macrophages in a colitis model (Song et al 2017). From several lines of evidence, including the fact that M2 macrophages are known to promote tissue repair, and that M1 macrophages are greatly increased in chronic wounds such as diabetic ulcers, it is becoming clear that controlled regulation of macrophage phenotype is critical for proper wound healing (Hesketh et al 2017;Khanna et al 2010;Krzyszczyk et al 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have revealed that a high frequency of intraperitoneally infused MSCs aggregated with immune cells in the peritoneal cavity (Sala et al, 2015;Bazhanov et al, 2016). In addition, our previous studies have shown that < 0.5% of intraperitoneally injected MSCs were detected in the heart, lung, liver, spleen, kidney, brain, and colon tissues (Song et al, 2017b;Song et al, 2018). Based on these previous studies, it is tempting to speculate that most of intraperitoneally infused TNF-α-stimulated cAT-MSCs formed aggregates and ameliorated IBD at sites distant from the inflamed colon by releasing soluble factors such as TSG-6 and PGE 2 .…”
Section: Discussionmentioning
confidence: 95%
“…Kang et al and Chae et al also demonstrated that canine and feline MSCs secrete soluble immunomodulatory factors (Chae et al, 2017;Kang et al, 2008). In addition, our previous studies have shown that TSG-6 released from human and canine MSCs ameliorates colitis in mice Song et al, 2017b).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations